Suction Influence on Load–Settlement Curves Predicted by DMT in a Collapsible Sandy Soil - Saab, Alfredo Lopes [UNESP]; Rodrigues, André Luís de Carvalho [UNESP]; Rocha, Breno Padovezi; Rodrigues, Roger Augusto [UNESP]; Giacheti, Heraldo Luiz [UNESP] (MDPI, 2023)
The plate load test (PLT) is the most reliable in situ testing for studying the load–settlement behaviour of footings on unsaturated collapsible soils. In these soils, the suction profile is not constant along the depth, and the scale effect between the prototype and footing leads to different suction averages and, consequently, different data. One method to eliminate the effect of soil suction on the test data is to fully saturate the soil prior to the test, which is also recommended at the design process for footing on collapsible soils. However, the inundation process on PLTs is expensive and time-consuming, which makes this procedure difficult to incorporate into engineering practice. This study presents a device that can be attached to flat dilatometer (DMT) to allow local inundation of the soil as part of the in situ test campaign and obtain the DMT-constrained modulus (MDMT) for both natural and inundated conditions. The MDMT presented an average reduction of 56% from natural to inundated condition. This parameter can be used in a model to predict load–settlement curves by DMT data considering the suction influence on this behaviour. The curves obtained from the prediction model were compared to curves determined by PLT conducted under the same in situ conditions. Good agreement was found between the curves predicted by DMT and those measured by PLT for both conditions. The proposed procedure, which uses a device attached to the DMT blade, provides an investigation method to obtain the load–settlement curve under different suction conditions, which can help in the selection and performance prediction of shallow foundations, taking into account suction and collapse phenomenon-related problems.
Keywords: DMT; inundation; load–settlement curve; plate load test; unsaturated soil